OPTIMIZATION OF INTELLECTUAL CAPITAL AND ISLAMI CITY PERFORMANCE INDEX IN ISLAMIC COMMERCIAL BANKS IN INDONESIA - Abdul Halim (CV. Radja Publika, 2021)
This study aims to examine the effect of intellectual capital and Islamicity performance index on the profitability of Islamic Commercial Banks in Indonesia. The object of this research is Islamic Commercial Banks in Indonesia that are registered with the OJK during the 2018-2020 period. The data used in this study is panel data for 3 years. The population of this study is Islamic Commercial Banks in Indonesia, and the number of samples taken is 9 Islamic banks selected using purposive sampling technique. Intellectual capital and Islamicity performance index are proxied by profit sharing ratio (PSR) as independent variables, while profitability is proxied by Return On Assets (ROA) as the dependent variable. The analytical method used is panel data linear regression with the Fixed Effect Model (FEM) method. The results show that simultaneously, intellectual capital and the Islamicity performance index affect profitability. Partially, intellectual capital has a positive and significant effect on profitability, while the Islamicity performance index has a positive but not significant effect on profitability. Based on the test results of the coefficient of determination, the Adjust R Square value is 87.7%, indicating that intellectual capital and the Islamicity performance index are able to explain 87.7% of the variation in profitability of Islamic Commercial Banks in Indonesia. This research has important implications in exploring the factors that influence the profitability of Islamic Commercial Banks in Indonesia. The research results can be used as a reference for bank management in optimizing intellectual capital and Islamicity performance index to increase profitability. However, this research also has limitations, such as the limited number of samples and the limited research time period, so that further research can be conducted to dig deeper into the relationship between intellectual capital, Islamic performance index, and profitability of Islamic Commercial Banks in Indonesia.